Microorganisms, including presumptive nitrogen-fixing bacteria, in rhizospheres of fynbos plants and soils in Swartboskloof, Jonkershoek - Dreyer, Karin Susanna (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1992.